The Role of Teachers as Curriculum Developers through Classroom Action Research in Enhancing Learning Innovation at Fatahillah Senior High School Ciledug - Alini Syakira Putri; Sutarman (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
The role of teachers as curriculum developers has become increasingly important in the implementation of competency-based education and the Merdeka Curriculum. However, teachers’ participation in curriculum development continues to face several challenges, including limited reflective practice, insufficient professional training, and heavy administrative workloads. This study aims to analyse the role of teachers as curriculum developers through Classroom Action Research (CAR) in enhancing learning innovation at SMA Fatahillah Ciledug. The research employed a qualitative approach using a descriptive case study design. Participants included subject teachers, the vice principal for curriculum affairs, and the school principal, selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document analysis, while data analysis followed the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings indicate that teachers play a significant role as curriculum developers by adapting learning instruments, developing teaching modules, integrating digital media, and implementing innovative learning strategies based on reflective practice. Teachers actively involved in CAR demonstrated greater innovation in applying project-based, collaborative, and contextual learning approaches. CAR also contributed to improving teachers’ professional competence, reflective skills, and involvement in curriculum development. In addition, collaborative CAR supported interdisciplinary learning integration and strengthened the school’s culture of innovation. Nevertheless, the implementation of CAR still faces several obstacles, such as limited time, administrative burdens, and insufficient institutional support. Therefore, schools need to provide more systematic support by strengthening reflective and collaborative cultures alongside continuous professional development.